2002
DOI: 10.1002/aoc.375
|View full text |Cite
|
Sign up to set email alerts
|

Review: Biological methylation of less‐studied elements

Abstract: Biological methylation is an enzymatic process in which a methyl group is transferred from one atom to another. For elements having atomic number greater than 11, biological methylation has been most extensively studied for three elements: arsenic, mercury and sulfur. However, many other elements also undergo biological methylation but have received less attention. Recent work on these lessstudied elements and new applications of biological methylation to environmental remediation, along with a description of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
76
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 167 publications
0
76
0
Order By: Relevance
“…However, our study indicates that substantial and variable losses of trace elements may take place in peat bogs due to methylation and subsequent volatilization. Such potential losses via methylation processes need to be carefully considered for all elements that undergo methylation (amongst others Hg, Pb, Sb, As and Se 44 ), and may present a limitation for the use of peat bogs as archives of atmospheric trace element deposition.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study indicates that substantial and variable losses of trace elements may take place in peat bogs due to methylation and subsequent volatilization. Such potential losses via methylation processes need to be carefully considered for all elements that undergo methylation (amongst others Hg, Pb, Sb, As and Se 44 ), and may present a limitation for the use of peat bogs as archives of atmospheric trace element deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Two scenarios are plausible for bismuth methylation in the human body: a microbial pathway with participation of microorganisms present in the intestine and an endogenous pathway as described for arsenic and other elements (Thayer, 2002;Aposhian and Aposhian, 2006). Anaerobic incubation of feces samples obtained from volunteers after ingestion of bismuth showed that intestinal microorganisms are able to methylate bismuth ex vivo Michalke et al, 2007Michalke et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, alkylation often seems to considerably increase the toxic potential of metal(loid)s. Many studies have shown that in the environment methylated and also, in some cases, hydride species can be formed by different mechanisms and from a variety of metal(loid)s (Craig, 2003). In particular, microorganisms, e.g., bacteria and fungi, have been reported to be involved in this specific kind of conversion (Thayer, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms have been shown to be capable of methylating a wide range of metals including Ge, Cd, In, Sn, Hg, Tl, Pb, Bi, and Po as well as metalloids, including As, Se, Sb, and Te [2]. Of these…”
Section: Introductionmentioning
confidence: 99%